La viscosupplementazione nei pazienti emofilici - Falez, Francesco; La Cava, Filippo; Ciolli, Luigi; Ciompi, Alessandro (Lo Scalpello - Journal, 2019)
VISCOSUPPLEMENTATION IN HAEMOPHILIC PATIENTS We evaluated the results obtained from the treatment of 88 intraarticular hyaluronic acid injections in haemophilic arthropathy according to the parameters of pain, function, health and radiographic evaluation. In 58 joints there was an improvement in the conditions preceding the treatments, in 20 the joint disease was stabilised, in 10 the treatment was ineffective and 9 of these were subsequently operated. 36 patients repeated the cycle at a distance. No adverse effects. Haemophilic arthropathy in its mild or moderate forms of joint damage can be effectively treated with viscosupplementation.